Chronic Exertional Compartment Syndrome of the Forearm in an Elite Rower - S. O'hEireamhoin; J. F. Baker; M. Neligan (Case Reports in Orthopedics)
We report a case of chronic exertional compartment syndrome (CECS) affecting the volar forearm compartment of an elite rower. CECS of the forearm is a less well recognised entity than lower limb CECS. We describe a typical history and detail a potential treatment.